Nonsurgical management of UCL injuries is tentatively successful in overhead athletes: A critical appraisal of case series ulnar collateral ligament - Oakes, N.; Medina McKeon, J. M. (Journal of Athletic Training, 2019)
"Context: Since the inception of the "Tommy John", surgical management of the ulnar collateral ligament(UCL) is fairly standard; however, the invasive, costly, time-and intensive nature of UCL surgery may be restrictive to some athletes. Methods: Electronic databases( PubMed and EbscoHost) were searched through September 2018. Search terms included iterations of "ulnar collateral ligament", "elbow", injury", "nonsurgical" and "nonoperative". A hand search was performed. Studies were limited to peer-reviewed articles, published in English after 2012. Selection criteria required that studies 1) included athletes; 2) investigated nonsurgical management of UCL injuries; 3) assessed outcomes associated with return-to-participation. Extracted data included frequencies of 1) returnto- play(RTP); 2) return-to-same level of play(RTSP); 3) athlete`s position; 4) complete reconstitution of the UCL; 5) the location of ligament rupture (proximal or distal)."RTP" was defi ned as any return to sporting activity. "RTSP" was the ability to return to the same level of play prior to injury. "Complete reconstitution" was defi ned as the lack of identifi able gaps in the UCL as visualized by MRI. Proportions of success/ failure for selected outcomes were calculated. Additionally, odds ratios(OR) [95% CI] were used to determine the association between tear location(proximal v. distal) and nonsurgical success. A 10-question critical appraisal tool, the JBI Critical Appraisal Checklist for Case Series(JBI), was used to evaluate evidence quality. Results: Seven studies met eligibility criteria. All were case-series. A total of 169 athletes underwent nonsurgical management of UCL injury in the 7 included studies. Sports included baseball, gymnastics, softball, hockey, volleyball, and tennis. A majority [n=71] were classifi ed as "elite". Overall, 83% (n=140) and 72% (n=121) were able to RTP or RTSP, respectively. For a proximal UCL tear, 82% (n=56) were able to RTSP, compared to 42% (n=13) for a distal UCL tear. For pitchers, 76% (n=38) were able to RTSP compared to 90% (n=9) of position players. For reconstitution of the UCL, 96% (n=23) were complete. For the effect of tear location, proximal tears were 650% (OR=6.5[2.5, 16.7], p<0.001) more associated with a successful outcome(RTSP or RTP). Included studies ranged from 5-10 on the JBI; 3 studies received a 10. "Failure to clearly describe clinic" was missed in 4 studies. "Consecutive patient inclusion" and "complete patient inclusion" in 2 studies. Conclusions: Based on the pooled outcomes of included studies, nonsurgical management of a UCL injury was reasonably successful RTP and RTSP rates in elite athletes, with better chance of success for proximal tears compared to distal. Although there was good success across outcomes, only case series studies were identifi ed for inclusion. The exploratory nature of utilizing nonsurgical management for UCL sprains in athletes, by way of the case series, appears to be fairly well established. An upgrade in study design, perhaps to level of clinical trials, is warranted."